Moderating Effects Of Marital Status And Dependent Count On Job Stress That Influence Job Productivity (International Journal of Food and Nutritional Sciences, 2022)
The pandemic has once again revealed the vulnerability at work places and have forced workforce to reevaluate their work priorities. Many reports highlight the post covid phenomenon of the great resignation as workforces’ world over want to quit jobs or switch jobs. Companies need to understand the pulse of the work force. The tech workforce constitute of 28.8% of women globally. The role of women has changed from that of a homemaker to a working woman, and one of the highly attractive sectors is Information Technology. This sector has about one-third of women employees among the total four million IT employees and so it is important to focus the study on this segment. The present study identifies nine factors that influence Job Stress and four factors that influence job productivity of women employees in selected IT companies. The exploratory factor analysis, and regression analysis was done to analyze the data. Organizations that identify and address these stressors can improve on employee’s productivity. Also it has wider impact on the psychological and social well being in the society. The regression model used for Job stress and productivity is considered as a good fit where the job stress factors shows 53.2% variance in productivity.